The Integrated Approach to Sustainable Development: The Case of Energy Efficiency and Solid Waste Management - Vertakova, Yulia V.; Plotnikov, Vladimir A. (International Journal of Energy Economics and Policy, 2019)
The purpose of this article is to explore the possibilities and develop proposals for the integrated solution of some of the problems of sustainable development related to waste processing and improving the energy efficiency of the economy. This purpose was achieved by solving the following objectives: 1) analysis of the problem of energy efficiency and how to solve it; 2) study of the problem of waste management and approaches to its solution; 3) development of proposals for the implementation of energy-efficient waste treatment. The leading methods used in the article were the following: a review of the literature, statistical analysis, expert assessments, systems, technological and institutional analysis, economic modeling. As a result of the study, it was proved that the problems of energy efficiency of the economy and waste management should not be solved in isolation, but in a comprehensive manner. The key idea of the study was that waste may be an unconventional (alternative) energy source. The existing technological solutions for their implementation require significant investments, changes in regulation, as well as transformation of the behavior of the population. Modernization of waste management often comes down to the modernization of landfill management. This is not effective enough (from environmental, economic, energy efficiency positions). The development of new institutional rules and innovative technologies is required. The authors propose to use waste as an energy resource using the technology of thermal catalytic depolymerization. In addition to the beneficial environmental effect, the proposed technology has high energy efficiency. Keywords: Energy Efficiency of the Economy, Waste, Sustainable Development, Energy Efficient Technology. JEL Classifications: Q01, Q42, Q53 DOI: https://doi.org/10.32479/ijeep.8009